Cervicogenic headache: a narrative review - Pereira, Kleber Fernando; Botelho, Wesley Gabriel Novaes; Pagliarin, Luiz Gustavo; Cesar, Alcântara Ramos de Assis (Headache Medicine, 2022)
Objective: To contextualize cervicogenic headache describing its etiology, pathophysiology, clinical picture, diagnostic criteria and treatments, to guide medical society in the face of the pathology that is increasing in its incidence. Methods: The study carried out searches in the PubMed, Nature, Scielo and Wiley databases, using the descriptors cervicogenic headache, and works published between the years 1980 and 2022 were analyzed, in all languages, in addition to the respective English translations. As an inclusion factor, it was considered: "works published within the scope of the study within the mentioned time interval and related to cervicogenic headache and as an exclusion factor: "works not related to the study topic and with reports already outdated according to current literature”. Results: 1,319 articles were found, analyzing the articles, 27 articles were selected, and according to their relevance in the subject, they are part of the scope of the work. In relation to cervicogenic headache, it is possible to classify it as a secondary headache, attributed to cervical disorders, with heterogeneous symptomatology, usually presenting as a unilateral, non-throbbing and non-excruciating headache, which may be triggered by trigger points in the cervical region and may still be present themselves with autonomous prodomes. Its etiology and pathophysiology are directly linked to cervical disorders and irritation of C1-C2-C3 afferent fibers, in addition to the convergence to the cervical trigeminal nucleus, increasing the variability of symptoms. Its diagnosis is based on diagnostic criteria and there are a wide variety of treatments with limited effectiveness. Conclusion: Cervicogenic headache can present in heterogeneous forms, making its diagnosis difficult and being underdiagnosed and erroneously treated in up to 50% of cases, its increase as a result of the pandemic alerts to the improvement in the diagnosis and treatment of cervicogenic headache and associated musculoskeletal disorders.